English Need Analysis for Mataram Children Forum in Mataram City - Haliza, Alda Nurul; Wilian, Sudirman; Farmasari, Santi; Sujana, I Made (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
As an international language, English has become highly important in supporting Mataram Children Forum (MCF) members' participation in raising children's voices at the national and international levels. However, there is no program that can help to develop their understanding of English skills. This research aims to find out the English levels and English needs of MCF members, the population of which were all members of the MCF while the samples are all the 15 active members with 3 additional samples from facilitators selected through a purposive sampling technique. All data were collected using triangulation techniques, including tests with the CEFR guideline, interviews, and questionnaires. They are then analyzed qualitatively and quantitatively based on the data specifications. The research reveals that (i) the members’ level of English was still low (7% at the pre-beginner level, 47% at the beginner level, 33% at the elementary level, and 13% at the intermediate level); (ii) their basic need is to be able to communicate orally in order to participate in the fulfillment of children's rights; (iii) their desire is to be able to communicate and understand English not just for organizational purposes, but also to help them in achieving their future goals; (iv) they tend to have issues in English comprehension, particularly at speaking and listening skills, which limits their level of participation. Therefore, it is recommended that the MCF members make an English learning program that could help meets their needs and function in raising children voice.